Selective BET bromodomain inhibition as an antifungal therapeutic strategy - Flore Mietton (Nature Portfolio, 2017)
BET proteins bind chromatin through their bromodomains (BDs) to regulate transcription and chromatin remodelling. Here, the authors show that the BET protein Bdf1 is essential for the fungal pathogenCandida albicans, and report compounds that inhibit the Bdf1 BDs with high selectivity over human BDs.